Increased Epicardial Fat Tissue Is a Marker of Subclinic Atherosclerosis in Ankylosing Spondylitis - Nilgun ÜSTÜN,; Mustafa KURT,; Nesrin ATCI,; Erman YAĞIZ,; Hayal GÜLER,; Ayse TURHANOĞLU, (Archives of Rheumatology, 2014)
Objectives: This study aims to assess subclinical atherosclerosis markers such as epicardial fat thickness, carotid intima media thickness (CIMT), and aortic stiffness index (ASI) in ankylosing spondylitis (AS) patients as well as to investigate the relationship between the subclinical atherosclerosis markers and disease activity/function/mobility indices. Patients and methods: Twenty-six AS patients (22 males, 4 females; mean age 43 years) and 26 age- and sex-matched healthy controls (21 males, 5 females; mean age 43 years) were included. Patients and controls with any reported cardiovascular disease or other comorbidities were excluded. Disease activity, functional capacity and spinal mobility were measured using the Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, and Bath Ankylosing Spondylitis Metrology Index, respectively. All patients underwent complete transthoracic echocardiographic examination including epicardial fat thickness and ASI, and sonographic examination including CIMT. Results: There were no significant differences in demographical and cardiovascular characteristics between AS patients and healthy controls (p>0.05). Epicardial fat thickness (5.15±1.13 vs. 4.11±1.22; p=0.003), CIMT (0.70±0.16 vs. 0.60±0.10; p=0.012) and ASI (14.2±10.8 vs. 8.6±3.1; p=0.018) were significantly increased in patients with AS compared to the healthy controls. There was no significant correlation between the subclinical atherosclerosis markers and disease activity/function/mobility indices (p>0.05). Conclusion: A significantly increased epicardial fat thickness, CIMT, and ASI were observed in AS patients compared with healthy controls.